- #1
foranlogan2
- 18
- 0
can anyone help?? in quantum mechanics commutator prove [L^x,L^y] = ihL^z
given
:L^x =(y^(pz)^-z^(py)^)
:L^y =(z^(px)^-x^(pz)^)
:L^z =(x^(py)^-y^(px)^) where ^ is just showing its operator
prove comutator [L^x,L^y] = ihL^z
I am swamped at every hurdle and can't seem to get my head around this question to find the answe of ihL^z . any help would be very much appreciated
given
:L^x =(y^(pz)^-z^(py)^)
:L^y =(z^(px)^-x^(pz)^)
:L^z =(x^(py)^-y^(px)^) where ^ is just showing its operator
prove comutator [L^x,L^y] = ihL^z
I am swamped at every hurdle and can't seem to get my head around this question to find the answe of ihL^z . any help would be very much appreciated